2004
DOI: 10.1309/dkk2-b9v4-n0w2-6a8q
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Ultrasound-Guided Fine-Needle Aspiration Cytology Diagnosis of Solid-Pseudopapillary Tumor of the Pancreas : A Rare Neoplasm of Elusive Origin but Characteristic Cytomorphologic Features

Abstract: Clinical histories, endoscopic ultrasound (EUS)-guided fine-needle aspiration (FNA) material, and immunohistochemical stains performed on cell block samples of 6 solid-pseudopapillary tumors of the pancreas (SPTPs) were reviewed in the cases of 5 females (13-58 years) and 1 man (57 years); all had abdominal pain. Preliminary cytologic diagnoses at endoscopy included 1 SPTP 2 low-grade neoplasms, and 3 pancreatic endocrine tumors. Variable numbers of branching fragments with central capillaries and myxoid strom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
96
0
8

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 52 publications
8
96
0
8
Order By: Relevance
“…In recent years various cases of solid pseudopapillary tumor have been described where ICC reached the right diagnosis on EUS- FNA-collected samples (30)(31)(32)(33): most were vimentin+ and cytokeratin+, whereas chomogranin and NSE were negative (they may be focally positive though) (34).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years various cases of solid pseudopapillary tumor have been described where ICC reached the right diagnosis on EUS- FNA-collected samples (30)(31)(32)(33): most were vimentin+ and cytokeratin+, whereas chomogranin and NSE were negative (they may be focally positive though) (34).…”
Section: Discussionmentioning
confidence: 99%
“…Bardales et al reported what to our knowledge is 1 of the larger case series pooled from more than 1 institution. 15 In their report, 5 of 6 cases of SPN were initially considered to be either PEN or another low-grade tumor. Similar to their report, 3 of the 5 SPN cases in the current study initially were considered as either PEN or suspicious for PEN by unsuspecting pathologists.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13] SPN is a pancreatic neoplasm whose cytologic features have been characterized previously. [14][15][16][17] Despite this, SPN continues to pose significant diagnostic challenges, even for experienced and often unsuspecting cytopathologists. In the current study, we report that recognition of clear cytoplasmic vacuoles in EUS-FNA samples are a useful clue with which to distinguish SPN from its closest morphologic mimicker, pancreatic endocrine neoplasm (PEN).…”
mentioning
confidence: 99%
“…EUS-guided FNA cytological analysis reveals characteristic branching papillae with myxoid stroma, best seen in cellblock material (33). When identified, regardless of the stage, resection should be considered.…”
Section: Solid Pseudopapillary Tumorsmentioning
confidence: 99%